2017
DOI: 10.1161/circulationaha.117.030583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Remote Heart Rhythm Sampling Using the AliveCor Heart Monitor to Screen for Atrial Fibrillation

Abstract: BACKGROUND:Asymptomatic atrial fibrillation (AF) is increasingly common in the aging population and implicated in many ischemic strokes. Earlier identification of AF with appropriate anticoagulation may decrease stroke morbidity and mortality. METHODS:We conducted a randomized controlled trial of AF screening using an AliveCor Kardia monitor attached to a WiFi-enabled iPod to obtain ECGs (iECGs) in ambulatory patients. Patients ≥65 years of age with a CHADS-VASc score ≥2 free from AF were randomized to the iEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
324
8
17

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(391 citation statements)
references
References 41 publications
6
324
8
17
Order By: Relevance
“…7 The participants were randomized to AliveCor KardiaMobile single lead electrocardiography screening twice weekly over 12 months (plus additional electrocardiography if symptomatic) or routine care. In this study, 19/500 patients in the screening group were diagnosed as having atrial fibrillation over the 12 month study period compared with 5/501 patients in the routine care group (hazard ratio 3.9; P=0.007).…”
Section: Newer Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The participants were randomized to AliveCor KardiaMobile single lead electrocardiography screening twice weekly over 12 months (plus additional electrocardiography if symptomatic) or routine care. In this study, 19/500 patients in the screening group were diagnosed as having atrial fibrillation over the 12 month study period compared with 5/501 patients in the routine care group (hazard ratio 3.9; P=0.007).…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Several studies have shown the efficacy of these devices for atrial fibrillation screening in populations at risk (table 3). 731323334353637383940…”
Section: Applications Of Newer Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 1001 older patients in the REHEARSE-AF study (Assessment of Remote Heart Rhythm Sampling Using the AliveCor Heart Monitor to Screen for Atrial Fibrillation), patients randomized to self-screening using a consumer, hand-held ECG device 1× to 2× weekly (and prn symptoms) demonstrated a hazard ratio of 3.9 for the detection of AF at 12 months, compared with patients receiving routine care. 11 And in the ASSERT-II study (Prevalence of SubClinical Atrial Fibrillation Using an Implantable Cardiac Monitor in Patient With Cardiovascular Risk Factors), the authors used implantable loop recorders to assess the prevalence of subclinical AF among 256 patients at increased risk of AF. 12 The investigators identified at least 5 minutes of subclinical AF among 34.4% of patients per year over mean follow-up of 16 months.…”
Section: Af Screeningmentioning
confidence: 99%
“…However, while they may be useful as alternatives to older patient-applied recorders at the time of symptomatic periods, or as a means to detect long-lasting paroxysms of AF, because of the brief and intermittent nature of their monitoring capabilities they are not optimal options for the detection of silent AF in the overwhelming majority of patients who are at risk, or for adequately evaluating AF burden, and have yields that do not compare with those of the prospective trials discussed below that utilized insertable monitors. 31 Prospective studies of silent AF Notably, device-detected silent AF is not limited to studies in patients with pacemakers/ICDs or post-stroke patients. Recently, three prospectively performed trials have been reported that considered patients with risk markers for AF and for stroke who demonstrated no prior history of AF, incorporating long-term monitoring (in years) with an implanted/inserted cardiac monitor (ICM) ( Table 1).…”
Section: Methods and Duration Of Monitoring For Silent Afmentioning
confidence: 99%